A young female of systemic lupus erythematosus with hepatic necrosis - Shahin, Md Abu; Sultan, Mohammad Imtiaz; Sultana, Nadia; Saeed, Atia; Yeasmin, Sabrina; Choudhury, Minhaj Rahim (Bangladesh Medical Journal, 2016)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of unknown etiology which can affect the skin, joints, kidneys, lungs, nervous system and other organs of the body. Clinical and radiological liver diseases are uncommon in patients with SLE. We report a 40-year-old female with known SLE presented with fever, severe abdominal pain, progressive abdominal distension, vomiting & absence of bowel movement for 4 days. Laboratory tests revealed thrombocytopenia, elevated ALT, AST, Alkaline phosphatase and high titer anti ds-DNA. USG revealed mild hepatosplenomegaly. serum bilirubin, serum electrolyte, serum amylase, 24 hour urinary amylase and serum lipase were normal. Serum anti phospholipid antibody was negative. Computed tomography (CT) of abdomen showed hypodense lesions in the liver that mimicked multiple liver abscesses and CT abdominal angiography showed hepatic infarction. She was treated with pulse methylprednisolone followed by high dose oral prednisolone and intravenous pulse cyclophosphamide. Patient improved clinically; platelet count & liver enzymes returned to the normal range. This patient represents a rare case of SLE who had hepatic vasculitis mimicking multiple liver abscesses. Bangladesh Med J. 2015 Jan; 44 (1): 43-45